Prospective Primary School Teachers' Perspectives on Environmental Education, Cultural Heritage, and Values Education: An Action Research Study - Gürhan, Ethem (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
In today's globalized world, rapid population growth, technological advancement, digital dependency, overconsumption of natural resources, and increasing environmental pollution have significantly influenced cultural values' erosion. While technology facilitates daily life, it threatens public health and disrupts ecological systems. This study employs an action research design to integrate core cultural values—rooted in Turkish-Islamic philosophy—into the educational experiences of prospective primary school teachers through environmental education. In a primary school in Konya, Türkiye, the research utilized semi-structured interviews to investigate the effects of value-based and environmental education activities on pre-service teachers. Data were analyzed using descriptive and content analysis methods. The findings reveal that the activities produced positive outcomes by reawakening long-forgotten values and enhancing the participants' environmental sensitivity. The study demonstrates that action-based learning experiences significantly contribute to future educators' ethical and ecological awareness.